Passion as the Pathway: Empowering Gen Z to Speak Up - Gita Widya Laksmini Soerjoatmodjo (Fakultas Psikologi Universitas Yudharta Pasuruan, 2026)
This study investigates the role of work passion as a psychological mechanism linking psychological empowerment and voice behavior among Gen Z employees. A cross-sectional survey was conducted involving 360 respondents using validated measures of psychological empowerment, work passion, and voice behavior. Structural Equation Modeling (SEM) was employed to examine both the direct and indirect relationships among the variables. The findings indicate that psychological empowerment positively predicts voice behavior. In addition, work passion partially mediates the relationship between psychological empowerment and voice behavior, suggesting that empowerment may foster voice behavior not only directly but also through the development of stronger motivational attachment to work. These findings highlight the importance of fostering internal motivation to support empowerment-driven voice behavior among young professionals. This study contributes to the literature on motivation and voice behavior while also offering practical implications for organizations seeking to create supportive work environments for Gen Z employees.